Job Hopping Behaviour and Turnover Intention on Millennial Teachers: A Closer Look to Their Antecendents - Juliana Juliana; Suwarto Suwarto; Rudy Pramono; Martinus Tukiran (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2021)
Abstract: Job Hopping Behaviour and Turnover Intention on Millennial Teachers: A Closer Look to Their AntecendentsThe purpose of this research is to examine the impacts of job satisfaction, psychological capital and the perceived organizational support on the turnover intention or job-hopping behaviour among the millennial teachers. The data collection is done by having a survey using questionnaires sent to 86 teachers who belong to the millennial group age and have been working between one to three years in the respective schools. A quantitative approach was used using PLS-SEM method with the assistance of Smart PLS 3.2.7 software to evaluate the outer model and the inner model. The results show that there are negative significant effects from perceived organizational support and psychological capital on turnover intention or jobhoppingbehaviour and no significant effect from the job satisfaction on the turnover intentionof the millennial teachers.Abstrak: Perilaku Lompat Kerja dan Intensi Pergantian Guru Milenial: Pandangan Lebih Dekat ke PendahulunyaTujuan dari penelitian ini adalah untuk menguji pengaruh kepuasan kerja, modal psikologis dan dukungan organisasi yang dirasakan terhadap turnover intention atau job-hopping behavior di kalangan guru milenial. Pengumpulan data dilakukan dengan cara survey menggunakan kuesioner yang dikirimkan kepada 86 guru yang termasuk dalam kelompok usia milenial dan telah bekerja antara satu sampai tiga tahun di sekolah masing-masing. Pendekatan kuantitatif menggunakan metode PLS-SEM dengan bantuan software Smart PLS3.2.7 untuk mengevaluasi outer model dan inner model. Hasil penelitian menunjukkan bahwa terdapat pengaruh negatif yang signifikan dari persepsi dukungan organisasi dan modal psikologis terhadap turnover intention atau perilaku berpindah kerja dan tidak ada pengaruh signifikan dari kepuasan kerja terhadap turnover intention guru milenial.